Prevalence of lactic acidosis in cattle and treatment response in Dinajpur district - Roy, BN; Islam, MF; Zohara, BF (Bangladesh Veterinarian, 2019)
Cattle admitted as outpatients at the Upazila (Sub-district) Veterinary Hospital in Dinajpur district headquarter and adjacent farms were examined clinically for lactic acidosis, observing loss of appetite, rumen hypo-motility or atony, dehydration, acidaemia, diarrhoea, depression, incoordination, collapse, and recumbency in severe cases. Out of 424 cattle examined, 21 were diagnosed as lactic acidosis and were categorized on the basis of sex, breed and age. Affected animals were grouped into three. Group A was treated with stomachic mixture/sodium bicarbonate orally (Zymovet(R) Each sachet contains Ammonium Bicarbonate 5 gm, Sodium Bicarbonate 13 gm, Nux vomica 1.4 gm, Ginger Powder 300 mg, Gentian Powder 300 mg: The ACME Laboratories, Veterinary Division, Dhamrai, Dhaka, Bangladesh) and purgatives; Group B was treated with stomachic mixture/sodium bicarbonate orally and parenterally. Group C was treated with stomachic mixture/sodium bicarbonate orally and parenterally with antibiotic (oxytetracycline). The prevalence of lactic acidosis in indigenous and crossbred animals was 4.4 and 7.3%, respectively. Group C animals recovered more quickly. It is suggested that encouraging intake of hay or straw just before and after a concentrate meal will reduce the prevalence. The Bangladesh Veterinarian (2019) 36(1 - 2): 20-24